Single-cell atlas of dental pulp stem cells exposed to the oral bacteria Porphyromonas gingivalis and Enterococcus faecalis - Zhang, Wen; Xu, Tiansong; Li, Xueying; Zhang, Yifei; Zou, Xiaoying; Chen, Feng; Yue, Lin (Frontiers in Cell and Developmental Biology, 2023)
Porphyromonas gingivalis and Enterococcus faecalis promote the development of pulpitis and periapical periodontitis. These bacteria are difficult to eliminate from the root canal systems, leading to persistent infection and poor treatment outcomes. We explored the response of human dental pulp stem cells (hDPSCs) to bacterial invasion and the mechanisms underlying the impact of residual bacteria on dental pulp regeneration. We depicted a single-cell transcriptome atlas of hDPSCs stimulated by P. gingivalis or E. faecalis. Single-cell sequencing was used to categorize the hDPSCs into clusters based on their response to P. gingivalis and E. faecalis. The most differentially expressed genes in the Pg samples were THBS1, COL1A2, CRIM1, and STC1, which are related to matrix formation and mineralization, and HILPDA and PLIN2, which are related to the cellular response to hypoxia. A cell cluster characterized by high expression levels of THBS1 and PTGS2 was increased after P. gingivalis stimulation. Further signaling pathway analysis showed that hDPSCs prevented P. gingivalis infection by regulating the TGF-β/SMAD, NF-κB, and MAPK/ERK signaling pathways. Differentiation potency and pseudotime trajectory analyses showed that hDPSCs infected by P. gingivalis undergo multidirectional differentiation, particularly to the mineralization-related cell lineage. Furthermore, P. gingivalis can create a hypoxia environment to effect cell differentiation. The Ef samples were characterized by the expression of CCL2, which is related to leukocyte chemotaxis, and ACTA2, which is related to actin. There was an increased proportion of a cell cluster that was similar to myofibroblasts and exhibited significant ACTA2 expression. The presence of E. faecalis promoted the differentiation of hDPSCs into fibroblast-like cells, which highlights the role of fibroblast-like cells and myofibroblasts in tissue repair. We identified the mechanism underlying the infection of hDPSCs by P. gingivalis and E. faecalis. Our results will improve understanding of the pathogenesis of pulpitis and periapical periodontitis. Furthermore, the presence of residual bacteria can have adverse effects on the outcomes of regenerative endodontic treatment.